2013
DOI: 10.22579/20112629.3
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la poda sobre la producción y calidad de frutos de Vitis vinifera L. Var. Sauvignon blanc en Sutamarchán – Boyacá

Abstract: El manejo de la producción, con ayuda de los sistemas de poda, es un factor fundamental a tener en cuenta para la obtención de cosechas de calidad para elaboración de vino. El objetivo de la investigación fue evaluar el efecto de la poda sobre la producción y la calidad de frutos de Vitis vinifera L. Var. Sauvignon Blanc en Sutamarchán -Boyacá, además de conocer el sistema de poda que genera la mejor producción y calidad organoléptica en la uva destinada a la elaboración de vino. La poda mixta presento los mej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In terms of number of clusters, the LYS system had 32 % more (P<0.05), which represents a greater number of fruiting points. To compare pruning types in this study, it was found that when more shoots were left, they produced a higher number of clusters per plant, higher fresh weight of clusters and yield, higher total soluble solids content and lower total titratable acidity and yielded the most adequate concentrations in probable degrees of alcohol (12.73 and 12.65 %) (Walteros, Constanza-Molano, Almanza-Merchán, Camacho-Helber, & Balaguera-López, 2012).…”
Section: Leaf and Cluster Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of number of clusters, the LYS system had 32 % more (P<0.05), which represents a greater number of fruiting points. To compare pruning types in this study, it was found that when more shoots were left, they produced a higher number of clusters per plant, higher fresh weight of clusters and yield, higher total soluble solids content and lower total titratable acidity and yielded the most adequate concentrations in probable degrees of alcohol (12.73 and 12.65 %) (Walteros, Constanza-Molano, Almanza-Merchán, Camacho-Helber, & Balaguera-López, 2012).…”
Section: Leaf and Cluster Layersmentioning
confidence: 99%
“…Número de capas de hojas (NCH), Número de racimos (NDR), Número de racimos internos (NDRI), Número de racimos externos (NDRE), Número de hojas externas (NDHE), Número de hojas internas (NDHI). Walteros et al (2012) compared pruning types and found that when more shoots are left, produces the most adequate concentrations in probable alcohol content and total soluble solids concentration.…”
Section: Comportamiento Agronómicomentioning
confidence: 99%